Analysis of response of epidermal melasma to 70% glycolic acid peel - Sadagopan, Kumaravel; Chintakula, Namratha (International Journal of Research in Dermatology, 2020)
Background: Melasma is an acquired disorder which presents as light brown to dark muddy brown macules (hypermelanosis) symmetrically and bilaterally on face mainly in areas which are exposed to sun and is seen more commonly among women. Chemical peels are said to be second line of management in melasma among which glycolic acid peel is considered as a gold standard. Aim of present study was to analyse the therapeutic response of epidermal melasma to 70% glycolic acid peel. Methods: 30 subjects were included in the study. Baseline melasma area and severity index (MASI) score of each epidermal melasma patient was recorded and were treated with 70% glycolic acid peel once in 3weeks for 3months and analysed response after 3 months using MASI scores. Results: Peak incidence of melasma was seen between age groups 31-40 years with female to male ratio 9:1, malar pattern being the most common pattern with majority of the patient’s duration of illness >1 year. 30% had positive family history. 26.6% had history of daily sun exposure >1 hour. 63% reduction of MASI score present. Most common side effects were erythema and burning. Conclusions: 70% glycolic acid along with sunscreen showed significant results in the improvement of melasma with 63% reduction in MASI score 12.97±5.15 to 4.69±1.92.